Proposta de um modelo de medição e avaliação de desempenho como ferramenta de gest ão - um estudo de caso num órgão público - Dantas, Aline Soares (2011)
The public sector performance has received much attention in the literature and due to that the purpose of this work is to develop a proposal for a model of performance measurement for a higher education institution unit. First, we performed a theoretical research on public organizations and private institutions of higher education, followed by a literature review on performance measurement and evaluation. This review presents some performance models that are quite frequent in the literature: Total Quality Management (Total Quality Management) - TQM and the PDCA cycle, SMART System, Balanced Scorecard and Môdef Ouanturn. In order to verify the possibility of implementing a performance measurement model for Higher Education Institutions, it was conducted a case study in a support unit of a University, located in the city of Natal, RN, Brazil. The study attempted to identify the key processes of the unit and proposed by the use of Quantum model in order to improve the management and operation of the same. The work aims to contribute to the advancement of knowledge in measurement and performance evaluation in higher education institutions that where still lacks scientific production of this subject compared to other areas. This study also identifies better practices and opportunities for improvement in processes to determine the expected performance indicators to aid a decision-making unit.